A checklist of the family Ichneumonidae (Hymenoptera: Ichneumonoidea) from Vietnam - Nhi, Pham Thi; Long, Khuat Dang (Academia Journal of Biology, 2016)
The ichneumonid fauna of Vietnam has been studied since early 20th century, but the records of this large insect group were published in the scattered papers. In this paper ichneumonid wasps from Vietnam are reviewed and a checklist of publishing species with local and world distribution is provided. Up to now, 185 ichneumonid species in 65 genera of 16 subfamilies are recorded from Vietnam. Of this number, no less than 56 species proved was described from Vietnam fauna only. In the checklist, the information of valid name, the first citation, holotype deposition and synonyms that used previously in Vietnam is provided. In addition, ten species are recorded for the first time in Vietnam, viz. Acerataspis clavata (Uchida, 1934); Charops brachypterus (Cameron, 1897); Chlorocryptus purpuratus (Smith, 1852); Chrionota townesi Uchida, 1957; Enicospilus hirayamai Uchida, 1955; Enicospilus melanocarpus Cameron, 1905; Lathrolestes roerichi Reschikov, 2011; Lytarmes maculipennis (Smith, 1858); Sachtlebenia sexmaculata Townes, 1963 and Stenichneumon appropinquans (Cameron, 1897). Additionally, there are 25 species listed with information about their hosts, being agricultural pests controlled to some degree by these parasitoids. This paper provides useful information for further studies on one of the largest family within Hymenoptera from Vietnam. Received 17 November 2016, accepted 5 December 2016, published online 6 December 2016